Rodent models for nicotine withdrawal. (October 2021) - Chellian, Ranjithkumar; Behnood-Rod, Azin; Bruijnzeel, Dawn M; Wilson, Ryann; Pandy, Vijayapandi; Bruijnzeel, Adriaan W
Background: Animal models are critical to improve our understanding of the neuronal mechanisms underlying nicotine withdrawal. Nicotine dependence in rodents can be established by repeated nicotine injections, chronic nicotine infusion via osmotic minipumps, oral nicotine intake, tobacco smoke exposure, nicotine vapor exposure, and e-cigarette aerosol exposure. The time course of nicotine withdrawal symptoms associated with these methods has not been reviewed in the literature. Aim: The goal of this review is to discuss nicotine withdrawal symptoms associated with the cessation of nicotine, tobacco smoke, nicotine vapor, and e-cigarette aerosol exposure in rats and mice. Furthermore, age and sex differences in nicotine withdrawal symptoms are reviewed. Results: Cessation of nicotine, tobacco smoke, nicotine vapor, and e-cigarette aerosol exposure leads to nicotine withdrawal symptoms such as somatic withdrawal signs, changes in locomotor activity, anxiety- and depressive-like behavior, learning and memory deficits, attention deficits, hyperalgesia, and dysphoria. These withdrawal symptoms are most pronounced within the first week after cessation of nicotine exposure. Anxiety- and depressive-like behavior, and deficits in learning and memory may persist for several months. Adolescent (4–6 weeks old) rats and mice display fewer nicotine withdrawal symptoms than adults (>8 weeks old). In adult rats and mice, females show fewer nicotine withdrawal symptoms than males. The smoking cessation drugs bupropion and varenicline reduce nicotine withdrawal symptoms in rodents. Conclusion: The nicotine withdrawal symptoms that are observed in rodents are similar to those observed in humans. Tobacco smoke and e-cigarette aerosol contain chemicals and added flavors that enhance the reinforcing properties of nicotine. Therefore, more valid animal models of tobacco and e-cigarette use need to be developed by using tobacco smoke and e-cigarette aerosol exposure methods to induce dependence.